1973
DOI: 10.1079/bjn19730063
|View full text |Cite
|
Sign up to set email alerts
|

Kwashiorkor in western Nigeria: a study of traditional weaning foods, with particular reference to energy and linoleic acid

Abstract: I. The fatty-acid composition of the plasma total lipids of children with kwashiorkor and of healthy infants was determined by gas-liquid chromatography. Breast milk from Yoruba mothers, and traditional weaning foods, were also analysed for fatty acids, and for protein, fat and carbohydrate.z. Evidence of essential fatty acid (EFA) deficiency was obtained in the children with kwashiorkor. The proportions of linoleic and arachidonic acids were reduced in the plasma lipids, whereas the endogenous eicosatrienoic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 12 publications
1
32
1
Order By: Relevance
“…5,6 Moreover, children can recover effectively on diets that would be considered low in protein. 7 The plasma protein concentration is often not particularly low in children with oedema, and during rehabilitation the oedema may clear without any change in serum albumin concentration.…”
Section: Metabolic Changes In Young Children With Protein-energy Malnmentioning
confidence: 99%
“…5,6 Moreover, children can recover effectively on diets that would be considered low in protein. 7 The plasma protein concentration is often not particularly low in children with oedema, and during rehabilitation the oedema may clear without any change in serum albumin concentration.…”
Section: Metabolic Changes In Young Children With Protein-energy Malnmentioning
confidence: 99%
“…The standard biochemical index to assess EFA deficiency is the triene/tetraene (20:3/20:4) ratio in which a ratio greater than 0.4 is indicative of EFA deficiency. In the earliest study of essential fatty acid deficiency in kwashiorkor, Naismith 68 noted a mean triene:tetraene ratio of 1.08 among 20 individuals with kwashiorkor. None of the control subjects had a trien:tetraene ratio greater than 0.4, whereas all of the infants with kwashiorkor had ratios greater than 0.4.…”
Section: Kwashiorkor and Protein Calorie Malnutritionmentioning
confidence: 99%
“…Other studies have since reported similar findings. [68][69][70] Although the consequences of EFA deficiency have not been fully defined, EFAs are essential components of phospholipids and may perhaps contribute to the development of fatty liver by affecting the hepatic biosynthesis of lipoproteins, which require the phospholipid derivative, phosphotidylcholine (discussed below). 39 …”
Section: Kwashiorkor and Protein Calorie Malnutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…These foods include yam (Dioscorea spp. ), rice (Oryza sativa), gari (fermented cassava grits), and cocoyam (Xanthosoma sagittifolium), which may be eaten with sauce or soup (Morley et al, 1969;Naismith 1973). These foods are usually mashed, thinned, or pre-chewed.…”
Section: Introductionmentioning
confidence: 99%